[Teaching Materials about the U.S. Constitution.] - Commission on the Bicentennial of the United States Constitution, Washington, DC.; Commission on the Bicentennial of the United States Constitution, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
Issued by the Commission on the Bicentennial of the United States Constitution, this collection of instructional materials is designed to help teach about the United States Constitution. The documents include: "Plant a Living Legacy"; "Teaching Guide to Accompany United States Presidents, 1789-1989"; "Skills Handbook: 200 Years of the U.S. Congress 1789-1989"; "Skills Handbook: Happy 200th Birthday, The United States Congress"; "Educational Programs of the Commission on the Bicentennial of the United States Constitution"; "To Establish Justice"; "200 Years of the Judiciary, 1790-1990"; "Equal Justice Under Law"; (A Pocket) Constitution of the United States; "With Liberty and Justice for All"; "Skills Handbook: Happy 200th Birthday, The U.S. Supreme Court"; and the March 1990 Newsletter of the Commission on the Bicentennial of the United States Constitution. Oversize replicas of the U.S. Constitution and Bill of Rights have not been reproduced here. (DB)
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Citizenship Education; Civics; Constitutional History; Constitutional Law; Elementary Secondary Education; Instructional Materials; Law Related Education; Learning Activities; Social Studies; Teaching Guides; Teaching Methods; United States History; United States Constitution; Supreme Court; Guides, Classroom -- Teacher